CircPUM1 Knockdown Confers Radiosensitivity in Oral Squamous Cell Carcinoma by Regulating the miR-580/STAT3 Pathway - Jia, Linghui; Huang, Pengcheng; Lin, Tingting; Lin, Chunyan; Ding, Xiaofen; Lin, Liping; Zhu, Lifeng; Zhou, Zhilian (Frontiers in Genetics, 2022)
Background: CircPUM1 acts as an oncogene in a variety of tumors, and there is no related research on oral squamous cell carcinoma. This study aimed to evaluate the clinical significance of circpum1 in oral squamous cell carcinoma radiotherapy. Methods: Radio-resistant cell lines were established by increasing the X-ray dose. Analysis of CircPUM1 expression in oral squamous cell carcinoma using bioinformatics tools. Cell proliferation was analyzed with CCK-8 and colony formation. Protein and gene expression were detected by western blotting and qPCR. RNA interference inhibits endogenous gene expression. A luciferase reporter system and immunoprecipitation were used to validate the target of CircPUM1. Result: CircPUM1 was highly expressed in OSCC. The higher the expression level of CircPUM1 in OSCC, the worse the clinical features and prognosis. Knockdown of CircPUM1 enhances the sensitivity of OSCC cells to X-rays, and expression of exogenous CircPUM1 makes OSCC cells acquire radiation resistance. The absence of CircPUM1 blocked the cells in G0 / G1 phase and triggered apoptosis. The prediction of mir-580 binding site, luciferase reporter system and immunoprecipitation confirmed that mir-580 is the binding site of CircPUM1. In addition, STAT3 was predicted and confirmed as the binding site of mir-580. Overexpression of STAT3 partially attenuated the radiosensitivity of OSCC cells to knockdown of CircPUM1. Conclusion: CircPUM1 has oncogene expression profile in oral squamous cell carcinoma; Patients with high expression of CircPUM1 have less benefit from radiotherapy and need more frequent follow-up. In addition, CircPUM1 may be a potential therapeutic target for oral squamous cell carcinoma. The CircPUM1 / mir-580 / STAT3 axis has a certain effect on the radiosensitivity of OSCC. These results suggest that patients with low expression of CircPUM1 may gain more benefits.